2018
DOI: 10.1097/md.0000000000009772
|View full text |Cite|
|
Sign up to set email alerts
|

Clostridium difficile infection in hospitalized patients with inflammatory bowel disease

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
1
10

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 58 publications
1
22
1
10
Order By: Relevance
“…di cile may explain recurrent course and poorer outcomes in IBD patients. [16,17] All isolates in the present study resisted cipro oxacin, and nearly all of these also resisted levo oxacin with the highest MICs (≥ 32 µg/ml − 1 ), resembling the hospital-acquired CDI in China. [5][6][7]9] However, merely 13.4% of isolates in IBD patients exhibited a resistance to moxi oxacin, which was signi cantly lower, when compared with the hospitalacquired CDI in China.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations
“…di cile may explain recurrent course and poorer outcomes in IBD patients. [16,17] All isolates in the present study resisted cipro oxacin, and nearly all of these also resisted levo oxacin with the highest MICs (≥ 32 µg/ml − 1 ), resembling the hospital-acquired CDI in China. [5][6][7]9] However, merely 13.4% of isolates in IBD patients exhibited a resistance to moxi oxacin, which was signi cantly lower, when compared with the hospitalacquired CDI in China.…”
Section: Discussionmentioning
confidence: 55%
“…It has been suggested that the higher CDI in IBD patients could be partially explained by the increased CDI incidence in the general inpatient population. [11,16] It was also found that the CDI incidence in pediatric IBD patients was higher than that in adult IBD patients. As reported, IBD children had higher intermittent CDI, when compared to IBD adults.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In this study, the incidence of CDI among IBD patients was 24.6% (33/134) and was much higher than matched non IBD group. According to our knowldege, the infection rate of C. di cile in patients with IBD most studies reported in western countries is less than 10% and was much lower than this investigation [23,24]. The method they used to detect CDI was toxigenic culture or an algorithm, including glutamate dehydrogenase (GDH) and C. di cile toxin A or B (CDAB) with nucleic acid ampli cation testing (NAAT) as con rmatory test, respectively.…”
Section: Discussionmentioning
confidence: 68%